Pencacah Pakan Kambing Untuk Kelompok Ternak Sempurna Dusun XIII Desa Pulau Gambar - Naibaho, Penteris Rumissar P; Kamil, Idham; Tarigan, Jenny Sari; Situngkir, Anggiat (Yayasan Cita Cendikiawan Al Kharizmi, 2024)
Pulau Gambar Village is one of the villages located in Serbajadi District, Serdang Bedagai Regency. Most of the residents of this village depend on goat farming for their living. Almost every household has goats with a minimum of 15 animals. Farmers still use conventional livestock systems where the feed given to livestock is grass obtained from locations around the farm without being chopped. The percentage of grass wasted at the bottom of the cage is still quite large. Due to limited land, some breeders collect grass for animal feed from other villages as well. The solution offered is in the form of procurement of multi-purpose chopping machines and training in the use of equipment and maintenance as well as training in animal feed processing. By holding this activity, partner problems can be completely resolved, where the capacity of the chopping machine during PKM implementation can reach 500 kg per hour.